A tensile-resistant insulated cable

By using nano-scale toughening agent with superbranched silicone structure in insulated cables, the problem of deterioration of dispersion under doping of high concentrations of inorganic nanoparticles is solved, and the tensile resistance and insulation performance of the cable are improved, avoiding the negative impact of moisture absorption on material performance.

CN118852783BActive Publication Date: 2025-03-28GUANGDONG AOTONG SPECIAL CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411332030.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-03-28
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The dispersion of existing insulated cables deteriorates under high concentration inorganic nanoparticles, resulting in an increase in dielectric constant and a decrease in insulation performance. At the same time, the hydrophilicity of nanoparticles leads to moisture absorption, affecting material performance.

Method used

Atom-transfer radical polymerization is used to synthesize nano-sized toughening agents with hyperbranched silicone structures. By introducing siloxane structures into the hyperbranched structures and cross-linking with silane coupling agents, the dispersion and compatibility of the toughening agents are improved, and the tensile resistance and insulation properties of the cable are enhanced.

Benefits of technology

It effectively improves the tensile resistance and insulation properties of the cable, prevents the agglomeration of inorganic fillers, reduces the dielectric constant, and avoids the impact of moisture absorption on the material properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118852783B_ABST
    Figure CN118852783B_ABST
Patent Text Reader

Abstract

The invention discloses a stretch-resistant insulated cable, comprising a multi-strand twisted wire core, an insulating layer, a reinforcing layer and an outer sheath. The insulating layer comprises, by weight, 85-95 parts of linear low-density polyethylene, 8-15 parts of ethylene-octene elastomer, 1.8-2.5 parts of a silane coupling agent, 0.12-0.15 parts of an initiator, 0.5-1 parts of an antioxidant, 1.2-1.5 parts of stearic acid, 3-3.5 parts of zinc oxide, 2.4-2.8 parts of a catalyst and 0.8-1.3 parts of a toughening agent; the toughening agent is a nano-scale toughening agent with a hyperbranched siloxane structure. The present invention adopts atom transfer radical polymerization to synthesize a nano-scale toughening agent with a hyperbranched structure, introduces a siloxane structure into the hyperbranched structure, and when a silane coupling agent cross-links polyethylene, the siloxane inside the hyperbranched structure is hydrolyzed and converted into a cross-linked structure after reaction, and the external siloxane can be covalently bonded with the ethylene of the grafted silane coupling agent, which can effectively improve the dispersibility and compatibility of the toughening agent in the cable, and improve the tensile strength and insulation performance of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, in particular to a tensile-resistant insulated cable. Background Art

[0002] In today's power systems, polymer dielectrics are widely used as insulating materials for power equipment, and their electrical properties directly determine the quality of the equipment and system. In actual operation, power cables are in a complex environment of working electric fields, internal and external stresses, heat, and chemical corrosion, which can easily cause insulation aging. In extreme cases, they may even break down, endangering the safe and stable operation of the power system. With the increase in the transmission level and capacity of the power system, the working environment of the relevant insulating materials of power cables will become more severe. Research on new polymer insulating dielectric materials with excellent performance has become a hot topic today. The insulation layer is usually the weakest part of the cable in terms of tensile strength. It is mainly designed for electrical insulation rather than to withstand mechanical stress, but the damage to the insulation layer has a great impact on its electrical insulation capabilities.

[0003] Cross-linked polyethylene is widely used in the insulation layer of AC and DC high-voltage cables due to its excellent dielectric properties. Cross-linked polyethylene nanocomposites have the ability to inhibit the accumulation of space charges in the material, improve the overall insulation performance of the material, and enhance certain mechanical properties of the material. They have great development prospects. Among them, the inorganic fillers that have been studied more are MgO, SiO2, ZnO, TiO2, MMT, etc. Studies have shown that when the doping concentration is low and the appropriate doping particle size is selected, the dielectric constant of the polymer can be effectively reduced; but at high concentrations, inorganic nanoparticles agglomerate in cross-linked polyethylene due to poor dispersibility, resulting in the weakening of the binding effect of nanoparticles on polyethylene molecules and polar molecular groups. At the same time, since most nanoparticles have a higher dielectric constant than the polyethylene matrix, they have a greater impact on the overall dielectric constant of the material at high concentrations. In addition, the nanoparticles themselves have strong hydrophilicity, and the absorption of water will directly affect the various properties of the insulating material and threaten the safe operation of power equipment. Therefore, it is still necessary to develop a tensile-resistant insulating cross-linked polyethylene material for cable insulation to meet the requirements of tensile resistance and excellent insulation performance. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention adopts atom transfer radical polymerization to synthesize a nano-scale toughening agent with a hyperbranched siloxane structure, introduces a siloxane structure into the hyperbranched structure, and when the silane coupling agent cross-links the polyethylene, the siloxane inside the hyperbranched structure is hydrolyzed and converted into a cross-linked structure after reaction, and the external siloxane can be covalently bonded with the ethylene of the grafted silane coupling agent, which can effectively improve the dispersibility and compatibility of the toughening agent in the cable, and the special structure of the toughening agent can improve the tensile strength and insulation performance of the cable.

[0005] The technical scheme for achieving the purpose of the present invention is as follows: a tensile-resistant insulated cable, comprising a multi-strand twisted core, an insulating layer, a reinforcing layer, and an outer sheath, wherein the insulating layer comprises, by weight, 85 to 95 parts of linear low-density polyethylene, 8 to 15 parts of ethylene-octene elastomer, 1.8 to 2.5 parts of a silane coupling agent, 0.12 to 0.15 parts of an initiator, 0.5 to 1 parts of an antioxidant, 1.2 to 1.5 parts of stearic acid, 3 to 3.5 parts of zinc oxide, 2.4 to 2.8 parts of a catalyst, and 0.8 to 1.3 parts of a toughening agent; the toughening agent is a nano-scale toughening agent having a hyperbranched siloxane structure.

[0006] Specifically, the preparation method of the toughening agent is as follows: in a reaction kettle, 9 to 19 eq methacrylate monomer, 1 to 3 eq methacrylamide siloxane monomer, 0.5 to 1 eq hyperbranched initiator, 0.55 to 1.05 eq cuprous bromide, and 50 to 60 eq anhydrous anisole are added; after freeze-thaw degassing, 0.6 to 1.2 eq N,N,N',N'',N''-pentamethyldiethylenetriamine is added under a nitrogen atmosphere; the mixture is stirred at 55 to 65 ° C for 1 to 2 h; after the reaction is completed, oxygen is introduced under ice bath conditions; copper ions are removed by column chromatography; the resulting solution is concentrated, precipitated in cold methanol, filtered, and the solid product is collected and dried to obtain a toughening agent.

[0007] It should be noted that, in the washing steps involved in the present invention, the volume ratio of the washing solvent to the washing liquid is 1:5.

[0008] Preferably, the silane coupling agent is at least one of vinyl triethoxysilane and vinyl trimethoxysilane; the initiator is diisopropylbenzene peroxide; the antioxidant is one or both of antioxidant 1010 and antioxidant 2246; and the catalyst is dibutyltin dilaurate.

[0009] More preferably, the silane coupling agent is vinyltrimethoxysilane;

[0010] More preferably, the antioxidant is antioxidant 1010;

[0011] Preferably, the methacrylate monomer has the following molecular structure:

[0012] Formula I, wherein n=7-27; preferably, n=10-20

[0013] The methacrylamide siloxane monomer has the following molecular structure:

[0014] Formula II;

[0015] The hyperbranched initiator has the following molecular structure of formula III:

[0016] Formula III.

[0017] Specifically, the preparation method of the methacrylate monomer is as follows: under a nitrogen atmosphere, 1.0 eq of alcohol, 1.5-2.0 eq of triethylamine, and 20 eq of anhydrous toluene are added to a reactor, 1.5-2.0 eq of methacryloyl chloride is dissolved in 20 eq of anhydrous toluene under ice bath conditions, and then slowly added dropwise to the reactor, stirred and reacted at room temperature for 36-48 h, filtered, and the resulting solution was concentrated, dissolved in dichloromethane, washed 3 times with an aqueous sodium hydroxide solution, and the organic phase was collected and evaporated to obtain a methacrylate monomer.

[0018] Specifically, the alcohol is a straight-chain alcohol with a carbon chain length of 8 to 28.

[0019] Specifically, the concentration of the sodium hydroxide aqueous solution used in the preparation method of the methacrylate monomer is 1-2 mol / L.

[0020] Specifically, the preparation method of the methacrylamide siloxane monomer is as follows: under a nitrogen atmosphere, 1.0 eq of 3-aminopropyltrimethoxysilane, 1.5-2.0 eq of triethylamine, and 20 eq of anhydrous toluene are added to a reactor, 1.5-2.0 eq of methacryloyl chloride is dissolved in 20 eq of anhydrous toluene under ice bath conditions, and then slowly added dropwise to the reactor, stirring and reacting at room temperature for 36-48 h, filtering, concentrating the obtained solution, and purifying by column chromatography to obtain the methacrylamide siloxane monomer.

[0021] Optionally, the eluent is petroleum ether:ethyl acetate = 8:1~8:2.

[0022] Specifically, the preparation method of the hyperbranched initiator is as follows: under a nitrogen atmosphere, 1 eq of hydroxyethyl methacrylate, 1.2-1.3 eq of triethylamine and 40-50 eq of dichloromethane solvent are added to a reactor, 1.5-2.0 eq of 2-bromoisobutyryl bromide is slowly added dropwise to the reactor under ice bath conditions, and stirred at room temperature for 12-24 h. After the reaction is completed, the mixture is washed with a saturated sodium bicarbonate solution and a saturated sodium chloride solution in sequence, dried with anhydrous magnesium sulfate, and then separated and purified with a silica gel column to obtain a hyperbranched initiator.

[0023] The present invention also discloses a method for preparing the tensile-resistant insulated cable, comprising the following steps:

[0024] 1) Preparation of multi-strand twisted wire core: a multi-strand twisted wire core is obtained by wire drawing, annealing, twisting and compacting;

[0025] 2) Pre-preparation of the insulating layer: disperse the initiator in the silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into a 70-90 ℃ oven and dry them for 10-12 hours, then divide them into 4 equal parts, one part is mixed with the initiator, silane coupling agent and toughening agent, one part is mixed with the catalyst, one part is mixed with the antioxidant and stearic acid, and one part is mixed with zinc oxide, and put them into sealed containers and stand for 18-24 hours, and extrude them respectively using a twin-screw extruder to obtain mixed masterbatch;

[0026] 3) Extruded insulation layer: Add the mixed masterbatch into the preheated single screw extruder, extrude the material onto the multi-strand twisted wire core, cool it in a water bath, place the resulting material in a humid environment at room temperature for 3-4 days, and dry it after the self-crosslinking process of polyethylene is completed;

[0027] 4) Reinforcement layer: The mesh glass fiber is woven, wound, impregnated and cured on the insulation layer;

[0028] 5) Outer sheath: Thermoplastic polyurethane is extruded onto the reinforcement layer through a single screw extruder, and patterns are pressed on the surface after cooling.

[0029] Specifically, in step 2), the parameters of the twin-screw extruder are as follows: the temperature of the first section is 75-85°C, the second section is 85-95°C, the third section is 95-105°C, the fourth section is 115-125°C, the fifth section is 135-145°C, the die head is 155-165°C; the main engine speed is 200-240 r / min, and the feeding speed is 20-25 r / min.

[0030] Specifically, the parameters of the single screw extruder in step 3) are as follows: the temperature of the first section is 165-170°C, the second section is 175-180°C, the third section is 185-190°C, the fourth section is 195-200°C, and the main engine speed is 30-40 r / min.

[0031] Beneficial Effects

[0032] The invention provides a tensile-resistant insulated cable, wherein the insulating layer comprises components such as linear low-density polyethylene, ethylene-octene elastomer, silane coupling agent, initiator, antioxidant, stearic acid, zinc oxide, catalyst and nano-scale toughening agent with hyperbranched siloxane structure; wherein the toughening agent is a nano-scale toughening agent with hyperbranched siloxane structure, and after being extruded into an insulating layer, the hyperbranched siloxane layer can be hydrolyzed and condensed along with the cross-linking of polyethylene, wherein the hyperbranched siloxane layer of the inner core becomes a cross-linked structure due to the close distance between each other, and the hyperbranched siloxane layer of the outer shell is covalently bonded with the silane coupling agent grafted on the polyethylene chain, thereby improving the compatibility of the toughening agent and the dispersibility of the inorganic filler, and effectively preventing the agglomeration of the inorganic filler. In addition, there is a strong interaction and covalent bonding between the interface of the polymer matrix and the overall nanostructure of the toughening agent and the reactive groups of the hyperbranched siloxane layer of the shell, which anchors the polymer macromolecule chain and hinders the movement of the molecular chain or other polar groups, thereby reducing the dielectric constant of the polymer composite material; the main molecular structure is a hydrophobic structure, and there is no problem that inorganic nanoparticles affect the various properties of the insulating material due to water absorption. In addition, the hyperbranched structure provides excellent dispersibility and processing performance. As the water released by the water-generating agent during processing becomes a cross-linked structure with a soft chain in the core and a core-shell structure with active reactive groups in the shell, this structure is conducive to stress dispersion and energy absorption, thereby improving the toughness of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention provides a synthetic route and toughening mechanism of the toughening agent;

[0034] Figure 2 This is the H NMR spectrum of the methacrylate monomer 1 of the present invention;

[0035] Figure 3 This is the H NMR spectrum of the methacrylamide siloxane monomer of the present invention;

[0036] Figure 4 This is the H NMR spectrum of the hyperbranched initiator of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0039] The raw materials and equipment used in the embodiments and comparative examples are described as follows:

[0040] Linear low-density polyethylene: brand DFDA-7042, purchased from Wuhan Rongchuang Plastic Co., Ltd.;

[0041] Ethylene-octene elastomer: brand 8999, purchased from Dongguan Yucheng Plastic Chemical Co., Ltd.;

[0042] Initiator: dicumyl peroxide, purchased from Tianjin Chemical Reagent Factory No. 1;

[0043] Antioxidant: Antioxidant 1010, purchased from Dongguan Guangsiyuan Polyurethane Materials Co., Ltd.;

[0044] Dibutyltin dilaurate: product number 2022062710, purchased from Tesco Chemical Co., Ltd.;

[0045] Vinyltrimethoxysilane: product number A800523, purchased from Shanghai MacLean Biochemical Technology;

[0046] Stearic acid: product number CH0537, purchased from Hubei Chenghai Chemical Co., Ltd.;

[0047] Zinc oxide: product number A0820065, purchased from Dongguan Qiaoke Chemical Co., Ltd.;

[0048] Cuprous bromide: product number C804582, purchased from Shanghai MacLean Biochemical Technology;

[0049] N,N,N`,N`,N``-pentamethyldiethylenetriamine: product number N822749, purchased from Shanghai MacLean Biochemical Technology;

[0050] Octanol: Product No. O815144, purchased from Shanghai MacLean Biochemical Technology;

[0051] 1-Hexadecanol: Product No. H810872, purchased from Shanghai MacLean Biochemical Technology;

[0052] Octacosanol: product number O815168, purchased from Shanghai MacLean Biochemical Technology;

[0053] Methacryloyl chloride: product number M813491, purchased from Shanghai MacLean Biochemical Technology;

[0054] 3-Aminopropyltrimethoxysilane: purchased from Shanghai MacLean Biochemical Technology;

[0055] Hydroxyethyl methacrylate: product number H810855, purchased from Shanghai MacLean Biochemical Technology;

[0056] 2-Bromoisobutyryl bromide: product number B802437, purchased from Shanghai MacLean Biochemical Technology;

[0057] Methacrylate monomer 1: , n=7, homemade, preparation method is as follows:

[0058] Under a nitrogen atmosphere, 1.0 eq of octanol, 2.0 eq of triethylamine, and 20 eq of anhydrous toluene were added to the reactor. 1.8 eq of methacryloyl chloride was dissolved in 20 eq of anhydrous toluene under ice bath conditions and then slowly added dropwise to the reactor. The reaction was stirred at room temperature for 36 h, filtered, and the resulting solution was concentrated, dissolved in dichloromethane, washed three times with aqueous sodium hydroxide solution, and the organic phase was collected and evaporated to obtain methacrylate monomer 1.

[0059] Methacrylate Monomer 2: , n=15, homemade, preparation method is as follows:

[0060] Compared with the methacrylate monomer 1, the difference is that octanol is replaced by 1-hexadecanol.

[0061] Methacrylate monomer 3: , n=27, homemade, preparation method is as follows:

[0062] Compared with the methacrylate monomer 1, the difference is that octanol is replaced by octacosanol.

[0063] Methacrylamide Siloxane Monomer: , homemade, the preparation method is as follows:

[0064] Under nitrogen atmosphere, 1.0 eq of 3-aminopropyltrimethoxysilane, 2.0 eq of triethylamine, and 20 eq of anhydrous toluene were added to the reactor. 1.8 eq of methacryloyl chloride was dissolved in 20 eq of anhydrous toluene under ice bath conditions and then slowly added dropwise to the reactor. The reaction was stirred at room temperature for 36 h, filtered, and the resulting solution was concentrated. The eluent was petroleum ether: ethyl acetate = 8:1~8:2. The solution was purified by column chromatography to obtain methacrylamide siloxane monomer.

[0065] Hyperbranched initiator: , homemade, the preparation method is as follows:

[0066] Under nitrogen atmosphere, 1 eq hydroxyethyl methacrylate, 1.3 eq triethylamine and 50 eq dichloromethane solvent were added to the reactor, and 1.8 eq 2-bromoisobutyryl bromide was slowly added dropwise to the reactor under ice bath conditions and stirred at room temperature for 18 h. After the reaction, the mixture was washed with saturated sodium bicarbonate solution and saturated sodium chloride solution, dried over anhydrous magnesium sulfate, and separated and purified using a silica gel column to obtain a hyperbranched initiator.

[0067] Toughener 1

[0068] In a reaction kettle, 9 eq methacrylate monomer 1, 1 eq methacrylamide siloxane monomer, 1 eq hyperbranched initiator, 1.05 eq ketone bromide, and 60 eq anhydrous anisole were added. After freeze-thaw degassing 3 times, 1.2 eq N,N,N',N'',N''-pentamethyldivinyltriamine was added under a nitrogen atmosphere. The mixture was stirred at 60 °C for 2 h. After the reaction was completed, oxygen was introduced under ice bath conditions. Copper ions were removed by column chromatography. The obtained solution was concentrated, precipitated in cold methanol, filtered, and the solid product was collected and dried to obtain toughening agent 1.

[0069] Toughener 2

[0070] In a reaction kettle, 19 eq of methacrylate monomer 1, 3 eq of methacrylamide siloxane monomer, 0.5 eq of hyperbranched initiator, 0.55 eq of ketone bromide, and 60 eq of anhydrous anisole were added. After freeze-thaw degassing 3 times, 0.6 eq of N,N,N',N'',N''-pentamethyldivinyltriamine was added under a nitrogen atmosphere. The mixture was stirred at 60 °C for 2 h. After the reaction was completed, oxygen was introduced under ice bath conditions. Copper ions were removed by column chromatography. The obtained solution was concentrated, precipitated in cold methanol, filtered, and the solid product was collected and dried to obtain toughening agent 2.

[0071] Toughener 3

[0072] Compared with toughening agent 2, the difference lies in that methacrylate monomer 1 is replaced by methacrylate monomer 2.

[0073] Toughener 4

[0074] Compared with toughening agent 2, the difference lies in that methacrylate monomer 1 is replaced by methacrylate monomer 3.

[0075] Toughener 5

[0076] Compared with toughener 2, the difference is that 19 eq of methacrylate monomer 1 is replaced by 22 eq of methacrylate monomer 2, and no methacrylamide siloxane monomer is added.

[0077] The following is the test method of the performance parameters involved in the present invention:

[0078] Relative molecular weight: gel permeation chromatography-differential detector (Waters, USA);

[0079] Molecular weight distribution: gel permeation chromatography-differential detector (Waters, USA);

[0080] Hydrodynamic diameter: Dynamic light scattering

[0081] H-NMR spectrum: 400 MHz NMR instrument (Bruker, Germany);

[0082] Table 1 Characterization parameters of toughening agent

[0083]

[0084] Depend on Figure 2 , 3, 4 can confirm the successful synthesis of monomers; from the data in Table 1, it can be seen that the synthesized toughening agents 1~4 are all nanoparticles with a molecular weight between 10000 and 25000 and a molecular weight distribution above 1.5, which is in line with the molecular weight distribution range of common branched structures.

[0085] Embodiment 1~6

[0086] A tensile-resistant insulated cable, the preparation method of which comprises the following steps:

[0087] 1) Preparation of multi-strand twisted wire core: a multi-strand twisted wire core is obtained by wire drawing, annealing, twisting and compacting;

[0088] 2) Pre-preparation of the insulating layer: disperse the initiator in the silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into an oven at 80 °C for 12 h, and then divide them into 4 equal parts, one part is mixed with the initiator, silane coupling agent, and toughening agent, one part is mixed with the catalyst, one part is mixed with the antioxidant and stearic acid, and one part is mixed with zinc oxide. Put them into sealed containers and let them stand for 24 h, and extrude them using a twin-screw extruder in turn. The parameters of the twin-screw extruder are as follows: the temperature of the first section is 75-85 °C, the second section is 85-95 °C, the third section is 95-105 °C, the fourth section is 115-125 °C, the fifth section is 135-145 °C, and the die head is 155-165 °C; the main engine speed is 200-240 r / min, the feeding speed is 20-25 r / min, and the mixed masterbatch is obtained;

[0089] 3) Extruded insulation layer: Add the mixed masterbatch into the preheated single screw extruder. The parameters of the single screw extruder are as follows: the temperature of the first stage is 165~170℃, the second stage is 175~180℃, the third stage is 185~190℃, the fourth stage is 195~200℃, and the main engine speed is 30~40 r / min. Extrude the material onto the multi-strand twisted wire core, cool it in a water bath, and place the obtained material in a humid environment at room temperature for 4 days. After completing the self-crosslinking process of polyethylene, dry it;

[0090] 4) Reinforcement layer: The mesh glass fiber is woven, wound, impregnated and cured on the insulation layer;

[0091] 5) Outer sheath: Thermoplastic polyurethane is extruded onto the reinforcement layer through a single screw extruder, and patterns are pressed on the surface after cooling.

[0092] The tensile-resistant insulated cables of Examples 1 to 6 correspond to insulating layers 1 to 6, and the formulations of the insulating layers 1 to 6 are shown in Table 2.

[0093] Comparative Examples 1 to 3

[0094] A stretch-resistant insulated cable, the preparation method is the same as that of Examples 1 to 6, except that the insulating layer materials used are different. The stretch-resistant insulated cables of Comparative Examples 1 to 3 correspond to insulating layers 7 to 9, and the formulas of the insulating layers 7 to 9 are shown in Table 2.

[0095] Table 2 Insulation layer formula (mass / kg)

[0096]

[0097] The following performance tests were performed on the insulation layer materials of the tensile-resistant insulated cables of the embodiments and comparative examples. The results are shown in Table 3.

[0098] (1) Tensile strength: cut into 0.5 mm thick sheets and measured according to GB / T 2951.11-2008 “General test methods for insulation and sheath materials of electric and optical cables”;

[0099] (2) Elongation at break: Cut into sheets with a thickness of 0.5 mm and measure the elongation of the inner and outer sheath materials respectively according to GB / T 2951.11-2008 “General test methods for insulation and sheath materials of electric and optical cables”;

[0100] (3) Water absorption percentage: Cut the inner and outer sheath pipes with a length of 25 mm respectively and measure according to GB 1034-2008 "Plastics - Determination of water absorption";

[0101] (4) Dielectric constant: Cut into 100 mm*100 mm*1 mm sheets, and measure the inner and outer sheath materials respectively according to GBT 31838.6-2021 "Solid Insulating Materials: Dielectric and Resistance Properties";

[0102] (5) Heat aging performance: The elongation at break and the change rate of tensile strength after heat treatment at 135 °C for 168 h were determined according to the method of GB 2591.7. The calculation method is: (tensile strength before aging / elongation at break - tensile strength after aging / elongation at break) / tensile strength before aging / elongation at break × 100%.

[0103] Table 3 Physical properties of insulation layer

[0104]

[0105] It can be seen from the data in Table 3 that the mechanical properties and insulation properties of the insulating layer prepared in the embodiment are better than those of the insulating layer prepared in Comparative Example 2 without adding a toughening agent.

[0106] From the data of Examples 3, 5, and 6 in Table 3, it can be seen that as the alkyl chain of methacrylate in the toughening agent increases, the tensile strength decreases and the elongation at break increases; from the data of Examples 4 and 5, it can be seen that as the proportion of methyl methacrylate monomer in the toughening agent increases, the degree of crosslinking increases, resulting in an increase in tensile strength and a decrease in elongation at break; from the data of Comparative Example 1, it can be seen that the addition of branched toughening agent 5 obtained by polymerization of monomer methacrylate has a low improvement in the physical properties of the insulating layer and a decrease in the anti-aging performance; from the data of Comparative Example 3, it can be seen that adding too much toughening agent will result in an excessive degree of crosslinking, resulting in a decrease in tensile strength and elongation at break.

[0107] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A tensile-resistant insulated cable, comprising a plurality of twisted cores, an insulating layer, a reinforcing layer, and an outer sheath, characterized in that: The insulating layer comprises, by weight, 85-95 parts of linear low-density polyethylene, 8-15 parts of ethylene-octene elastomer, 1.8-2.5 parts of silane coupling agent, 0.12-0.15 parts of initiator, 0.5-1 parts of antioxidant, 1.2-1.5 parts of stearic acid, 3-3.5 parts of zinc oxide, 2.4-2.8 parts of catalyst, and 0.8-1.3 parts of toughening agent; the toughening agent is a nano-scale toughening agent having a hyperbranched siloxane structure; The preparation method of the toughening agent is as follows: in a reaction kettle, 9-19 eq of methacrylate monomer, 1-3 eq of methacrylamide siloxane monomer, 0.5-1 eq of hyperbranched initiator, 0.55-1.05 eq of cuprous bromide, and 50-60 eq of anhydrous anisole are added; after freeze-thaw degassing, 0.6-1.2 eq of N,N,N',N'',N''-pentamethyldiethylenetriamine is added under a nitrogen atmosphere; the mixture is stirred at 55-65° C. for 1-2 h; after the reaction is completed, oxygen is introduced under ice bath conditions; copper ions are removed by column chromatography; the obtained solution is concentrated, precipitated in cold methanol, filtered, and the solid product is collected and dried to obtain the toughening agent; The methacrylate monomer has the following molecular structure: Formula I, wherein n=7-27; The methacrylamide siloxane monomer has the following molecular structure: Formula II; The hyperbranched initiator has the following molecular structure of formula III: Formula III; the silane coupling agent is at least one of vinyltriethoxysilane and vinyltrimethoxysilane.

2. A tensile insulated cable according to claim 1, characterized in that: The initiator is dicumyl peroxide; the antioxidant is one or both of antioxidant 1010 and antioxidant 2246; and the catalyst is dibutyltin dilaurate.

3. A tensile insulated cable according to claim 1, characterized in that: The preparation method of the methacrylate monomer is as follows: under a nitrogen atmosphere, 1.0 eq of alcohol, 1.5-2.0 eq of triethylamine, and 20 eq of anhydrous toluene are added to a reaction kettle, 1.5-2.0 eq of methacryloyl chloride is dissolved in 20 eq of anhydrous toluene under ice bath conditions, and then slowly added dropwise to the reaction kettle, stirred and reacted at room temperature for 36-48 hours, filtered, concentrated, dissolved in dichloromethane, washed 3 times with sodium hydroxide aqueous solution, collected the organic phase, evaporated, and obtained the methacrylate monomer.

4. A tensile insulated cable according to claim 1, characterized in that: The preparation method of the methacrylamide siloxane monomer is as follows: under a nitrogen atmosphere, 1.0 eq of 3-aminopropyltrimethoxysilane, 1.5-2.0 eq of triethylamine, and 20 eq of anhydrous toluene are added to a reaction kettle, 1.5-2.0 eq of methacryloyl chloride is dissolved in 20 eq of anhydrous toluene under ice bath conditions, and then slowly added dropwise to the reaction kettle, stirring and reacting at room temperature for 36-48 h, filtering, concentrating the obtained solution, and purifying by column chromatography to obtain the methacrylamide siloxane monomer.

5. The tensile-resistant insulated cable according to claim 1, characterized in that: The preparation method of the hyperbranched initiator is as follows: under a nitrogen atmosphere, 1 eq of hydroxyethyl methacrylate, 1.2-1.3 eq of triethylamine and 40-50 eq of dichloromethane solvent are added to a reaction kettle, 1.5-2.0 eq of 2-bromoisobutyryl bromide is slowly added dropwise to the reaction kettle under ice bath conditions, and stirred at room temperature for 12-24 h. After the reaction is completed, the mixture is washed with a saturated sodium bicarbonate solution and a saturated sodium chloride solution in sequence, dried with anhydrous magnesium sulfate, and then separated and purified with a silica gel column to obtain a hyperbranched initiator.

6. A method for preparing a tensile-resistant insulated cable according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Preparation of multi-strand twisted wire core: a multi-strand twisted wire core is obtained by wire drawing, annealing, twisting and compacting; 2) Pre-preparation of the insulating layer: disperse the initiator in the silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into a 70-90 ℃ oven and dry them for 10-12 hours, then divide them into 4 equal parts, one part is mixed with the initiator, silane coupling agent and toughening agent, one part is mixed with the catalyst, one part is mixed with the antioxidant and stearic acid, and one part is mixed with zinc oxide, and put them into sealed containers and stand for 18-24 hours, and extrude them respectively using a twin-screw extruder to obtain mixed masterbatch; 3) Extruded insulation layer: Add the mixed masterbatch into the preheated single screw extruder, extrude the material onto the multi-strand twisted wire core, cool it in a water bath, place the resulting material in a humid environment at room temperature for 3-4 days, and dry it after the self-crosslinking process of polyethylene is completed; 4) Reinforcement layer: The mesh glass fiber is woven, wound, impregnated and cured on the insulation layer; 5) Outer sheath: Thermoplastic polyurethane is extruded onto the reinforcement layer through a single screw extruder, and patterns are pressed on the surface after cooling.

7. A method for preparing a tensile-resistant insulated cable according to claim 6, characterized in that: In step 2), the parameters of the twin-screw extruder are as follows: the temperature of the first section is 75-85°C, the second section is 85-95°C, the third section is 95-105°C, the fourth section is 115-125°C, the fifth section is 135-145°C, the die head is 155-165°C; the main engine speed is 200-240 r / min, and the feeding speed is 20-25 r / min.

8. The method for preparing a tensile-resistant insulated cable according to claim 6, characterized in that: In step 3), the parameters of the single screw extruder are: the temperature of the first section is 165~170 ℃, the second section is 175~180 ℃, the third section is 185~190 ℃, the fourth section is 195~200 ℃, and the main engine speed is 30~40 r / min.

Citation Information

Patent Citations

  • Siloxane modified urethane acrylate hyperbranched oligomer and preparation method thereof and multi-curing coating obtained therefrom

    CN101665561A

  • Polysiloxane-containing halogen-free environment-friendly flame-retardant polyolefin cable material and preparation method thereof

    CN102634107A